Downregulation of apelin in the human placental chorionic villi from preeclamptic pregnancies - Yamaleyeva, Liliya M.; Chappell, Mark C.; Brosnihan, K. Bridget; Anton, Lauren; Caudell, David L.; Shi, Sara; McGee, Carolynne; Pirro, Nancy; Gallagher, Patricia E.; Taylor, Robert N.; Merrill, David C.; Mertz, Heather L. (American journal of physiology: endocrinology and metabolism, 2015)
The role of the endogenous apelin system in pregnancy is not well understood. Apelin's actions in pregnancy are further complicated by the expression of multiple forms of the peptide. Using radioimmunoassay (RIA) alone, we established the expression of apelin content in the chorionic villi of preeclamptic (PRE) and normal pregnant women (NORM) at 36–38 wk of gestation. Total apelin content was lower in PRE compared with NORM chorionic villi (49.7 ± 3.4 vs. 72.3 ± 9.8 fmol/mg protein; n = 20–22) and was associated with a trend for lower preproapelin mRNA in the PRE. Further characterization of apelin isoforms by HPLC-RIA was conducted in pooled samples from each group. The expression patterns of apelin peptides in NORM and PRE villi revealed little or no apelin-36 or apelin-17. Pyroglutamate apelin-13 [(Pyr 1 )-apelin-13] was the predominant form of the peptide in NORM and PRE villi. Angiotensin-converting enzyme 2 (ACE2) activity was higher in PRE villi (572.0 ± 23.0 vs. 485.3 ± 24.8 pmol·mg −1 ·min −1 ; n = 18–22). A low dose of ANG II (1 nM; 2 h) decreased apelin release in NORM villous explants that was blocked by the ANG II receptor 1 (AT 1 ) antagonist losartan. Moreover, losartan enhanced apelin release above the 2-h baseline levels in both NORM and PRE villi ( P < 0.05). In summary, these studies are the first to demonstrate the lower apelin content in human placental chorionic villi of PRE subjects using quantitative RIA. (Pyr 1 )-apelin-13 is the predominant form of endogenous apelin in the chorionic villi of NORM and PRE. The potential mechanism of lower apelin expression in the PRE villi may involve a negative regulation of apelin by ANG II.